Does Disclosure Regulation Affect Mutual Fund Families’ Proxy Voting? - Kim, Eunjee (The Accounting Review, 2025)
ABSTRACT Nonactivist investors that own more than 5 percent of a firm must report their holdings by filing a 13G in which they must commit to not influencing control of the firm. Mutual fund families are the most common investors filing 13Gs. I study whether the 13G requirement affects mutual fund families’ voting in proxy contests. I find mutual fund families that file the form are less likely to vote for activist proposals than are those that do not, suggesting that the requirement discourages mutual fund families from supporting activists who seek to influence control of the firm. The effects strengthen when vote outcomes directly affect the firm’s control and when activists pose a higher threat to the firm. I further document that the aggregate voting power of 13G-filing mutual fund families correlates with management winning contested votes and retaining board seats during proxy contests. Data Availability: Data are available from the public sources cited in the text. JEL Classifications: G34; G23; G38; K22; L51; M12.